(untitled) (The Review of Diabetic Studies, 2025)
Prosthetics and orthotics (P&O) represent essential components of modern rehabilitation medicine, offering individuals with limb loss, neuromuscular disorders, or musculoskeletal impairments the opportunity to regain mobility, independence, and dignity. Over the past decade, advances in biomedical engineering, materials science, and digital health technologies have transformed the field, enabling the development of lighter, more durable, and functionally sophisticated devices. This comprehensive review examines the role of prosthetics and orthotics in enhancing mobility and quality of life, with a focus on functional outcomes, psychosocial well-being, and emerging innovations. Evidence demonstrates that appropriate use of prosthetic and orthotic devices significantly improves gait, posture, and daily activity performance, while also contributing to increased self-esteem, social integration, and employment opportunities. Furthermore, technological breakthroughs such as 3D printing, robotics, and artificial intelligence are reshaping device design, customization, and monitoring, promising more personalized and accessible solutions. Despite these advancements, challenges remain in terms of affordability, accessibility, and patient-centered design, particularly in low- and middle-income countries. The review highlights strategies to overcome these barriers and underscores the importance of interdisciplinary collaboration, policy support, and ongoing research. By integrating technological innovation with patient-centered rehabilitation, prosthetics and orthotics continue to play a transformative role in improving health outcomes and quality of life worldwide.